Pragmatics in English As a Lingua Franca Findings and Developments - Walkinshaw, Ian (Developments in English as a lingua franca ;, 2022)
This series welcomes book proposals detailing innovative and cutting edge research and theorisation in the field of English as a lingua franca (ELF). The purpose of the series is to offer a wide forum for work on ELF, including aspects such as descriptions and analyses of ELF; ELF use in a range of domains including education (primary, secondary and tertiary), business, tourism; conceptual works challenging current assumptions about English use and usage; works exploring the implications of ELF for English language policy, pedagogy, and practice; and ELF in relation to global multilingualism.